Personalizing radiation protection in medical imaging: an Islamic approach - Zainuddin, Zainul Ibrahim (IIUM Press, International Islamic University Malaysia, 2018)
This paper aligns the Islamic worldview and other Islamic essences to radiation protection. Current guidelines on radiation protection lack in terms of punitive measures as well as the existence of differences in addressing non-compliances to radiation protection practices. The Islamic stance is non-separation of religious matters from one’s daily life, including in the professional environment. In this paper Medical imaging practitioners are introduced to three elements of the Islamic worldview and the other essences that emerge from their discussions. Spirituality, religiosity, the concept of retribution, Maqasid and Qawaid Al-Shariah and guiding principles of Ihsan, Itqan, Fitrah and Istiqomah can help shape the Muslim practitioner to accept radiation protection as more than a professional obligation. The onus upon the Medical imaging practitioner to consolidate his practice should be seen within the context of motivation and deterrence that those essences carry. Personalizing radiation protection thus becomes a personal Muslim professional virtue.